Exploring The Relationship Between X and Y Generation Employees’ Fear Of Contracting Coronavirus And Their Holiday Purchase Intention - Doğan, Yunus; Ercik, Cevat (My University, 2023)
The study aims to put forward if there are any differences in the of uncertainty, anxiety, and stress levels experienced by X nd Y generation employees as a result of coronavirus as well as their holiday purchase intentions. In order to achieve this goal, 388 people over the age of 20 with a source of income were contacted, and data have been collected using questionnaire forms prepared on google forms. Within the scope of the study, T-Test and One-Way Anova analyses were utilized to evaluate the differences between the X and Y generation employees' fear of contracting coronavirus and their holiday purchase intention. As a result of the analyses, it was revealed that there is a significant difference between the X and Y generation employees at the 0.05 significance level. Simply put, it has been discovered that generation-Y employees are less bothered by thinking about coronavirus than generation-X employees, and generation-Y employees are more inclined than generation-X employees to purchase holidays if they could access to the possibilities in the future. Furthermore, it was asserted that the majority of the participants intend to purchase a holiday if they can afford it, despite the fact that the participants' degrees of uncertainty, anxiety, and stress as a result of coronavirus differ depending on their educational status. Ethics committee approval dated 03.03.2022/76 was obtained from Mersin University Social and Human Sciences Ethics Committee for the study.
Keywords: Covid 19; Generations; Fear of Contracting Coronavirus; Holiday Purchase Intention.